Energy-saving smart LED lighting - Ho, Hsiao Chong (Nanyang Technological University, 2022)
The increasing popularity of Smart LED lighting systems has emerged over the years with the focus on energy-saving and increasing the productivity of the consumers by providing accessibility. In this project, the report will be focusing on fabricating a prototype in showcasing one of the Nanyang Technological University hostels located at North hill as an improvement for their current hall conventional lighting system. The concept will realistically be catering to the needs of the students who live in a hostel. The system will have the capability of continuous human tracking using a passive infrared sensor (PIR) and a light-dependent resistor (LDR) for detecting the light ambient intensity to switch on or off LED light sources upon the motion status.